A Pre-Experimental Study on The Use of Group Counseling with Self-Management Techniques to Reduce Gadget Addiction among High School Students - Arifyanto, Alber Tigor; Nufi, Erma Pratiwi; Silondae, Dodi Priyatmo; Haidir, La Ode Ahmad; Tahir, M. Ridwan (KONSELOR, 2025)
The high prevalence of gadget addiction among adolescents, driven by uncontrolled device usage, highlights the need for alternative intervention methods. Group counseling offers students the opportunity to share experiences, provide mutual support, and learn new skills within a structured setting. Self-management is an essential skill for adolescents to regulate their time, emotions, and habits. Integrating self-management techniques into counseling sessions provides students with practical tools to independently control their gadget use, offering benefits both in the present and for long-term well-being. This study aims to examine the effectiveness of group counseling employing self-management techniques in reducing gadget addiction among students at SMA Negeri 5 Kendari, Southeast Sulawesi, Indonesia. A pre-experimental approach with a one-group pretest-posttest design was used. The participants consisted of 430 students who completed a gadget addiction scale. A purposive sampling technique was applied to select 9 students with high gadget addiction scores. Group counseling sessions were conducted six times, with each session lasting 90 minutes. Gadget addiction data were collected using a pre-test during the first session and a post-test in the sixth session. The counseling sessions addressed increasing awareness of healthy gadget use, understanding the adverse effects of gadget addiction, practicing self-management techniques, evaluating progress, strengthening commitment to sustained self-regulation, and creating a follow-up action plan. The results showed a significant decrease in gadget addiction scores from an initial average (pre-test) of 134.44 (63.41%) to a post-test score of 105.88 (49.94%), reflecting a reduction of 28.55 points or 13.46%. Inferential statistical analysis using the Wilcoxon Signed Rank test with a significance level of α = 0.05 yielded a P-value of 0.008. Since the P-value was less than α (0.008 < 0.05), the alternative hypothesis (Ha) was accepted, and the null hypothesis (Ho) was rejected. Therefore, it can be concluded that group counseling with self-management techniques is proven effective in reducing gadget addiction levels among students at SMA Negeri 5 Kendari.